PENGARUH MOTIVASI TERHADAP KINERJA ANGGOTA POLRI PADA POLSEK DANAU PANGGANG KABUPATEN HULU SUNGAI UTARA - Diana Hayati; Sri Mulyani (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, This research about motivation influence in improving performance at Polsek Danau Panggang Hulu Sungai Utara. Motivation variable influencing performance consisted of the achievement (X1), confessing (X2), work that self (X3), responsibilities (X4), opportunity for the forward (X5), Wages (X6), condition physical work (X7), observation (X8), relation/link with the friend work (X9), security (X10) and organizational policy (X11). Population in this research is entire commisioned Police member at Polsek Danau Panggang is as much 26 member. Model the regresi indicate that pursuant to test F as a whole the model of signifikan with the storey level signifikansi = 5 %. This matter is shown by F signifikansi = 0,044 which its value less than 0,05 Influence which is between variable X1, X2, X3, X4, X5, X6, X7, X8, X9, X10 And X11 to Y is signifikan of because sig 0,044 < 0,05. Pursuant to the examination hence variable X11 (organizational policy) having an effect on compared to by bigger of other variable that is equal to 0,836 %. Where about the value represent the biggest value among other factors. This fact indicate that in biggest factor field of influence and related/relevant /its with the performance of Police member in Polsek Danau Panggang is X11 that is organizational policy.